VD_FINDINFO ML / 2023 / 157 vom 20. November 2023 - VD Tribunal cantonal (2023)
OBLIGATION D'ENTRETIEN, MAINLEVÉE DÉFINITIVE, CONJOINT, ENFANT, MAJORITÉ{ÂGE}, CONCORDANCE, CRÉANCE | 133 al. 3 CC, 133 CC, 279 al. 1 CC, 279 CC, 289 al. 1 CC, 289 CC, 318 al. 1 CC, 318 CC, 80 al. 1 LP, 80 LP